Palladium-catalyzed allylation of carbonyl compounds with various allylic compounds using In-InCl3 in aqueous media - Jang, TS; Keum, G; Kang, SB; Chung, BY; Kim, Y (GEORG THIEME VERLAG KG, 2003)
Various allylic compounds can be effectively applied to palladium-catalyzed allylation of carbonyl compounds via the formation of pi-allylpalladium(II) intermediates and their transmetalation with indium in the presence of indium trichloride in aqueous media.
Keywords: BARBIER-TYPE ALLYLATION; INDIUM; TRANSMETALATION; ALDEHYDES; REAGENTS; ALCOHOLS